2005
DOI: 10.4269/ajtmh.2005.72.410
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Prevalence of the Plasmodium Falciparum Chloroquine Resistance Transporter 76t Marker Associated With Cessation of Chloroquine Use Against P. Falciparum Malaria in Hainan, People’s Republic of China

Abstract: The use of chloroquine treatment for Plasmodium falciparum malaria was abandoned in China in 1979 because of widespread drug resistance. Subsequent studies found decreases in the prevalence of chloroquine-resistant strains. To evaluate these decreases and assess the current status of chloroquine sensitivity in Hainan, China, we determined the prevalence of the P. falciparum chloroquine resistance transporter (PfCRT) 76T marker in the DNA of blood samples collected from 1978 to 2001. Results showed the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 19 publications
8
78
3
Order By: Relevance
“…For example, a region of Malawi known for highly prevalent CQR was repopulated with drug-sensitive parasites within 10 years after CQ use was stopped (17). Similar recovery of CQ-sensitive P. falciparum populations was recently reported in Kenya and has also been observed in China (18,19). These changes in the absence of drug pressure have been explained by fitness costs that are carried by CQ-resistant mutants (20).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…For example, a region of Malawi known for highly prevalent CQR was repopulated with drug-sensitive parasites within 10 years after CQ use was stopped (17). Similar recovery of CQ-sensitive P. falciparum populations was recently reported in Kenya and has also been observed in China (18,19). These changes in the absence of drug pressure have been explained by fitness costs that are carried by CQ-resistant mutants (20).…”
mentioning
confidence: 57%
“…* Patterns of pfcrt and pfmdr1 haplotypes in malaria endemic regions also depend on the fitness costs of these haplotypes relative to the advantages they offer to parasite populations. In Malawi and Hainan Island, China, where CQ-resistant CVIET parasites (Dd2-or GB4-type pfcrt) from the large Southeast Asian-African sweep had once been selected almost completely, populations of wild-type CQ-sensitive parasites characterized by the haplotype CVMNK (HB3-type pfcrt) returned after withdrawal of CQ (17,18). These findings suggest that CVIET mutants are at a fitness disadvantage to wild-type forms in the *Consistent with the pfcrt-pfmdr1 interactions described in this study, pfmdr1 codon 1246Y with possible synergistic or compensatory influence of 86Y or 184Y has also been associated with treatment failures after AQ monotherapy or after AQ plus ACT in Tanzania (53).…”
Section: G8mentioning
confidence: 99%
“…Recent studies from Malawi showed that a policy that removed chloroquine as an available treatment in 1993 was followed by repopulation of the region with chloroquine-sensitive strains by 2001 (111). A similar but slower return of chloroquine-sensitive strains has also been observed in Hainan, People's Republic of China, where use of the drug against P. falciparum malaria was suspended in 1979 (112).…”
Section: The Fall Of Chloroquine and Rise Of Artemisininsmentioning
confidence: 80%
“…In addition, chloroquine, although not used for treatment of falciparum malaria, can be used for infections that are thought to be P. vivax but are actually unrecognized mixed infections or misdiagnosed P. falciparum infections. 46 A large number of expatriates from the Indian subcontinent may import P. vivax infection.…”
Section: Discussionmentioning
confidence: 99%